2021
DOI: 10.1002/mrd.23475
|View full text |Cite
|
Sign up to set email alerts
|

Sperm morphometry is affected by increased inbreeding in the Retinta cattle breed: A molecular approach

Abstract: The effect of inbreeding depression on sperm motility is well documented, but its influence on sperm morphometry has been scarcely examined to date. Here, we combined the use of computer‐assisted sperm morphometry analysis (CASMA) with a SNP‐based genomic approach to determine and characterize the effect of inbreeding on the sperm shape of a highly inbred cattle population. We determined seven morphometric parameters on frozen‐thawed sperm samples of 57 Retinta bulls: length (L, µm), width (W, µm), area (A, µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Second, some individuals are more ‘resistant’ to the harmful effects of inbreeding on the phenotype (by harbouring a reduced depression load (Poyato‐Bonilla et al., 2020)), and therefore, they could remain in some herds despite their inbreeding values if their fertility is not affected. Finally, our previous studies evaluating the effect of inbreeding on the fertility of Retinta animals suggested that such decrease is associated with negative changes in sperm quality in bulls rather than an effect caused by the fertility of the cow (Dorado et al., 2017; Teran et al., 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Second, some individuals are more ‘resistant’ to the harmful effects of inbreeding on the phenotype (by harbouring a reduced depression load (Poyato‐Bonilla et al., 2020)), and therefore, they could remain in some herds despite their inbreeding values if their fertility is not affected. Finally, our previous studies evaluating the effect of inbreeding on the fertility of Retinta animals suggested that such decrease is associated with negative changes in sperm quality in bulls rather than an effect caused by the fertility of the cow (Dorado et al., 2017; Teran et al., 2021).…”
Section: Discussionmentioning
confidence: 96%
“…The morphometric analysis of the sperm head involves an assessment of size and shape and its relation to functionality (Valverde et al, 2016). Moreover, these parameters are linked to genetic factors, and the breed of the bull can influence results (Terán et al, 2021). Moreover, solutions in which sperm are suspended and processed can influence these variables and cause alterations in measurements depending on the semen extender used for the samples (Fernandes et al, 2021; Fernandez‐Novo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%